2018
DOI: 10.1105/tpc.17.00810
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Nitrogen Starvation Responses by Members of the Arabidopsis GARP-Type Transcription Factor NIGT1/HRS1 Subfamily

Abstract: Nitrogen (N) is often a limiting nutrient whose availability determines plant growth and productivity. Because its availability is often low and/or not uniform over time and space in nature, plants respond to variations in N availability by altering uptake and recycling mechanisms, but the molecular mechanisms underlying how these responses are regulated are poorly understood. Here, we show that a group of GARP G2-like transcription factors, NITRATE-INDUCIBLE, GARP-TYPE TRANSCRIPTIONAL REPRESSOR1/HYPERSENSITIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 78 publications
7
138
0
Order By: Relevance
“…We considered that the grafted scions were subject to inorganic nutrient starvation stress before forming the vasculature connection between the scion and stock, and examined the expression level of marker genes that respond to mineral nutrient starvation stress. We focused on the ERD5, SGT1 , and NRT2.5 genes of At among the nutrient deficiency responsive genes, reported previously (Hammond et al ., 2003; Kiba et al ., 2018), and identified their orthologs in Nb by tblastx search. The orthologs of Nb of AT3G30775 ( ERD5 ), AT2G43820 ( SGT1 ) and AT1G12940 ( NRT2.5 ) were Niben101Scf00390g02001, Niben101Scf05415g00003 and Niben101Scf12671g00007 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We considered that the grafted scions were subject to inorganic nutrient starvation stress before forming the vasculature connection between the scion and stock, and examined the expression level of marker genes that respond to mineral nutrient starvation stress. We focused on the ERD5, SGT1 , and NRT2.5 genes of At among the nutrient deficiency responsive genes, reported previously (Hammond et al ., 2003; Kiba et al ., 2018), and identified their orthologs in Nb by tblastx search. The orthologs of Nb of AT3G30775 ( ERD5 ), AT2G43820 ( SGT1 ) and AT1G12940 ( NRT2.5 ) were Niben101Scf00390g02001, Niben101Scf05415g00003 and Niben101Scf12671g00007 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This idea is supported by the work of (Ma et al, 2015) showing that the regulation of NRT2.4 and NRT2.5 by N starvation depends on CBL7, which is specifically induced by NO 3 - deficiency. Moreover, NIGT/HRS1s have been shown to act as transcriptional repressor of NRT2.4 and NRT2.5 upon NO 3 - treatment (Kiba et al, 2018)Safi et al 2018). Local regulation by NO 3 - would explain why these transporters, unlike NRT2.1 , are always repressed when plants are on 10 mM NO 3 - , regardless of the light conditions (Supplemental Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…HY5 has been recently identified as a regulator of NRT2.1 by mediating light promotion of NO 3 - uptake (Chen et al, 2016). HRS1, HHO1, HHO2 and HHO3 are repressors of NRT2.4 and NRT2.5 expression under high N conditions (Kiba et al, 2018)Safi et al 2018)…”
mentioning
confidence: 99%
“…Recent studies have found that NITRATE-INDUCIBLE, GARP-TYPE TRANSCRIPTIONAL REPRESSORs (NIGT1.1/1.2/1.3/1.4) downregulate the expression of genes induced by N starvation, including NRT2.1, NRT2.4, NRT2.5, AMT1;1, and AMT1;3. (Medici et al 2015;Kiba et al 2018;Maeda et al 2018). Therefore, we profiled the expression of all candidate genes that are repressed by NIGT1.2 and induced by N starvation, according to the list compiled by Kiba et al (2018) (Fig.…”
Section: Expression Of Genes Encoding Inorganic N Transporters In Rootsmentioning
confidence: 99%
“…Hu et al (2009) reported that the transcript levels of several nitrateresponsive genes are positively correlated with nitrate concentrations in A. thaliana roots. One such gene is the transcriptional repressor NIGT1.4, the translational product of which downregulates the expression of high-affinity N uptake transporters (Medici et al 2015;Kiba et al 2018;Maeda et al 2018). Accordingly, the high-affinity nitrate transporter gene NRT2.1, which is induced by nitrate during the PNR, was shown to be repressed by a nitratedependent feedback signal involving the NRT1.1/NPF6.3/CHL1 transceptor (Bouguyon et al 2015).…”
Section: Introductionmentioning
confidence: 99%